Realization and Evaluation of the Device for Measuring the Impedance of Human Body for Detecting the Respiratory and Heart Rate - Metshein, Margus; Parve, Toomas; Annus, Paul; Rist, Marek; Min, Mart (Elektronika ir Elektrotechnika, 2017)
The idea of a device for measuring the impedance of human body with the target of monitoring the respiratory and heart rate is proposed in this paper. Hardware realization of the proposed idea is described with the illustration of the custom designed printed circuit board. Preparation of electrode shirts with various electrode placement configurations is introduced. Series of experimental measurements in the cases of dynamic bioimpedance reference and single human subject are described and results shown to evaluate the custom made device. The excitation frequencies in the range of 2 MHz–20 MHz are utilized in the cases of large foil and textile electrodes to focus on the use of the capacitive connection to the object – constituting the novelty of the current paper. The results are analysed concerning the dependency of the visual availability of the interesting signal of breathing and heart rate of the material and the placement of the electrodes. Availability of breathing is found to be evident in all of the experimented cases. The heart rate is found to be challenging because of the presence of high frequency noise. DOI: http://dx.doi.org/10.5755/j01.eie.23.3.18330